Gender Communication For Disaster Education In Women’s Prison - Halimatu Sa'diah (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2022)
Disaster education is essential in creating a prison system that is resilient to disasters. However, it is still designed commonly in Indonesia and is not gender specific. This research emphasizes how crucial gender communication is for disaster education in prison, particularly in female prisons. This research aims to identify how gender is communicated during disaster education at Lapas Perempuan Kelas IIB Yogyakarta. It started with a research question on how the implementation of gender communication between women staff and women prisoners during disaster education. The method used in this study was a case study method used at Lapas Perempuan Kelas IIB Yogyakarta. Data was collected through observation, interviews, and document studies. The results discovered that the gender communication process during disaster education at Lapas Perempuan Kelas IIB Yogyakarta still did not completely accommodate women prisoners’ needs. This research highlights the relationship between gender issues and the women’s access to disaster management in Indonesia. The results are expected to encourage women’s participation in disaster management, also improve disaster education quality in women’s prisons.